Solar thin film cell and preparation method thereof
By uniformly distributing polystyrene spherical particles in the adhesive layer of the solar thin film battery, the problem of inconsistent height difference between the front plate glass and the CIGS thin film battery chip is solved, the uniform distribution of the adhesive film and the stability of the packaging are achieved, and the performance and life of the solar cell are improved.
Patent Information
- Application Number
- CN202411668852.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-03-18
AI Technical Summary
When manufacturing solar thin-film batteries, the height difference between the front plate glass and the CIGS thin-film battery chip is inconsistent, resulting in uneven distribution of the adhesive film after liquefaction, affecting the packaging effect, and may result in poor appearance, affecting the stability and reliability of the product.
By uniformly distributing polystyrene spherical particles in the film layer, the height difference between the front plate glass and the CIGS thin film battery chip is consistent, so as to ensure uniform distribution of the film after liquefaction and ensure uniform packaging.
The uniform distribution of the adhesive film is achieved, the bonding effect is improved, the stability and reliability of the packaging is enhanced, the power attenuation of solar cells is slowed, and the full life cycle of the module is extended.
Smart Images

Figure CN119653872A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a solar thin-film battery and a preparation method thereof. Background Art
[0002] In recent years, with the development of research and production technology, solar cells will play a significant role in the field of traditional energy. The current market mainly includes silicon-based solar cells, multi-compound thin-film solar cells, and organic dye-sensitized solar cells. Among them, silicon-based solar cells have become the leading product of solar cells due to their advantages in raw material reserves, and have maintained a large market share. Compared with other types of solar cells, the scientific research and production of silicon-based solar cells have been relatively mature and stable, and the photoelectric conversion efficiency is relatively high. In the next few years, the huge demand for photovoltaic power generation in countries around the world will drive the development momentum of silicon-based solar cells to remain strong. Although silicon-based solar cells have many advantages, the price of silicon raw materials is relatively high, which puts them in a relatively weak position in terms of price. Therefore, the invention of thin-film batteries has greatly reduced the cost of raw materials.
[0003] As the competition among major photovoltaic manufacturers intensifies, how to slow down the power attenuation of solar cells, ensure the stability of solar cell performance, and improve power generation efficiency has become a key research direction for major manufacturers. Research shows that for solar thin-film cells, the packaging effect is crucial to their performance. Solar thin-film cells use adhesive films to bond the front glass and CIGS thin-film cell chips (CIGS power generation glass). For adhesive films, please refer to Chinese patent CN201010160589.3. As the size of solar cells continues to lengthen and widen, the height difference between the two "glass plates" is difficult to maintain consistency. For large solar cells, if the height difference is not uniform, the distribution of the adhesive film after liquefaction is also not uniform, which affects the packaging effect and may cause appearance defects, which has an adverse effect on the stability and reliability of the product. Summary of the invention
[0004] The first technical problem to be solved by the present invention is to provide a solar thin-film battery, which utilizes polystyrene spherical particles to keep the height difference between the front glass and the CIGS thin-film battery chip consistent, thereby ensuring uniform distribution of the adhesive film after liquefaction and good packaging uniformity.
[0005] The second technical problem to be solved by the present invention is to provide a method for preparing the above-mentioned solar thin-film battery, which has simple steps, convenient operation, high efficiency, stable product performance and high yield.
[0006] To solve the first technical problem mentioned above, the present invention provides a solar thin-film battery, comprising a front glass layer, a film layer, and a CIGS thin-film battery chip layer stacked in sequence from top to bottom, wherein the film layer has a thickness of 0.2 to 0.7 mm, and the film layer is provided with uniformly distributed polystyrene spherical particles, and the polystyrene spherical particles are distributed in a single layer in the film layer.
[0007] Preferably, the coefficient of variation CV of the particle size of the polystyrene spherical particles in the film layer is less than 3.5%.
[0008] Preferably, the particle size of the polystyrene spherical particles in the adhesive film layer is between 50 and 1000 μm.
[0009] Preferably, the amount of polystyrene spherical particles added to the adhesive film layer is: 15-30 g of polystyrene spherical particles per square meter of the adhesive film layer.
[0010] A solar thin-film battery provided by the present invention utilizes polystyrene spherical particles to keep the height difference between the front glass and the CIGS thin-film battery chip consistent, thereby ensuring that the adhesive film is evenly distributed after liquefaction, making the CIGS thin-film battery chip and the front cover glass more fully bonded, with greater bonding force and better bonding effect, thereby improving packaging uniformity, ensuring better packaging effect, ensuring the stability of solar cell performance, improving power generation efficiency, ensuring the stability of component performance, slowing down the power attenuation of the component, and ensuring the full life cycle of the component.
[0011] In order to solve the second technical problem, the present invention provides a method for preparing the above-mentioned solar thin film battery, comprising the following steps:
[0012] (1) First, a CIGS thin-film battery chip is prepared, and then an adhesive film is laid on the CIGS thin-film battery chip to form an adhesive film layer;
[0013] (2) According to the width of the film layer, an appropriate number of special spray heads are arranged at equal intervals above the film layer to ensure that the spraying working surfaces of all the film spray heads are sufficient to evenly and completely cover the width of the entire film layer, and then the polystyrene spherical particles are evenly sprayed on the surface of the film layer through a number of special spray heads. During the spraying process, the running speed of the spray head is 1 m / s compared to the CIGS thin-film battery chip;
[0014] (3) Laying the corresponding front glass from top to bottom on the adhesive film sprayed with polystyrene spherical particles in step (2);
[0015] (4) After the lamination is completed, a lamination process is performed. The humidity requirement of the lamination process is 30% to 75% RH. The specific steps are as follows:
[0016] a. First, vacuumize the air. The vacuum pressure is -15Kpa~-1KPa and the vacuum time is 1~3min;
[0017] b. Then transfer to the lamination chamber, the temperature of the lamination chamber is 95-135°C, and the lamination time is 9-15 minutes;
[0018] c. Then transfer to the hot pressing chamber for hot pressing, the temperature of the hot pressing chamber is 140-165°C, and the hot pressing time is 8-15 minutes;
[0019] d. Finally, transfer to the cold pressing chamber for cold pressing. The temperature of the cold pressing chamber is 20-75°C and the cold pressing time is 6-12 minutes.
[0020] The present invention provides a method for preparing a solar thin-film battery using polystyrene spherical particles, which has simple steps, convenient operation, high efficiency, stable product performance and high yield. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 It is a schematic diagram of the layer structure of the solar thin film battery of the present invention.
[0022] Figure 2 It is a comparative line chart of the adhesion test of the same batch of products.
[0023] Figure 3 It is a scatter plot comparing power tests of products from the same batch.
[0024] Figure 4 This is a scatter plot comparing the power attenuation of the same batch of products after the DH1000 test. DETAILED DESCRIPTION
[0025] Embodiment 1:
[0026] See also Figure 1 A solar thin-film battery comprises a front glass layer 1, a film layer 2, and a CIGS thin-film battery chip layer 3 stacked in sequence from top to bottom, wherein the film layer 2 has a thickness of 0.2 mm, and polystyrene spherical particles 4 are evenly distributed in the film layer 2, and the polystyrene spherical particles 4 are distributed in the film layer 2 in a single layer.
[0027] The coefficient of variation CV of the particle size of the polystyrene spherical particles 4 in the adhesive film layer 2 is less than 3.5%.
[0028] The particle size of the polystyrene spherical particles 4 in the adhesive film layer 2 is between 50 and 100 μm.
[0029] The amount of polystyrene spherical particles 4 added to the adhesive film layer 2 is: 15 g of polystyrene spherical particles 4 per square meter of the adhesive film layer 2 .
[0030] The above-mentioned method for preparing a solar thin film battery comprises the following steps:
[0031] (1) First, a CIGS thin film battery chip is prepared, and then an adhesive film is laid on the CIGS thin film battery chip to form an adhesive film layer 2;
[0032] (2) According to the width of the film layer 2, an appropriate number of special spray heads are arranged at equal intervals above the film layer 2 to ensure that the spraying working surfaces of all the film spray heads are sufficient to evenly and completely cover the width of the entire film layer 2, and then the polystyrene spherical particles 4 are evenly sprayed on the surface of the film layer 2 through a number of special spray heads. During the spraying process, the running speed of the spray head is 1 m / s compared to the CIGS thin film battery chip;
[0033] (3) Covering the corresponding front glass from top to bottom on the adhesive film sprayed with the polystyrene spherical particles 4 in step (2) for lamination;
[0034] (4) After the lamination is completed, a lamination process is performed. The humidity requirement of the lamination process is 30% RH. The specific steps are as follows:
[0035] a. First, vacuumize the air with a pressure of -15Kpa and a vacuum time of 1min;
[0036] b. Then transfer to the lamination chamber, the temperature of the lamination chamber is 95°C, and the lamination time is 9 minutes;
[0037] c. Then transfer to the hot pressing chamber for hot pressing. The temperature of the hot pressing chamber is 140°C and the hot pressing time is 8 minutes;
[0038] d. Finally, transfer to the cold pressing chamber for cold pressing. The temperature of the cold pressing chamber is 20℃ and the cold pressing time is 6 minutes.
[0039] Embodiment 2:
[0040] See also Figure 1 A solar thin-film battery comprises a front glass layer 1, a film layer 2, and a CIGS thin-film battery chip layer 3 stacked in sequence from top to bottom, wherein the film layer 2 has a thickness of 0.5 mm, and polystyrene spherical particles 4 are evenly distributed in the film layer 2, and the polystyrene spherical particles 4 are distributed in the film layer 2 in a single layer.
[0041] The coefficient of variation CV of the particle size of the polystyrene spherical particles 4 in the adhesive film layer 2 is less than 3.5%.
[0042] The particle size of the polystyrene spherical particles 4 in the adhesive film layer 2 is between 450 μm and 550 μm.
[0043] The amount of polystyrene spherical particles 4 added to the adhesive film layer 2 is: 23 g of polystyrene spherical particles 4 per square meter of the adhesive film layer 2 .
[0044] The above-mentioned method for preparing a solar thin film battery comprises the following steps:
[0045] (1) First, a CIGS thin film battery chip is prepared, and then an adhesive film is laid on the CIGS thin film battery chip to form an adhesive film layer 2;
[0046] (2) According to the width of the film layer 2, an appropriate number of special spray heads are arranged at equal intervals above the film layer 2 to ensure that the spraying working surfaces of all the film spray heads are sufficient to evenly and completely cover the width of the entire film layer 2, and then the polystyrene spherical particles 4 are evenly sprayed on the surface of the film layer 2 through a number of special spray heads. During the spraying process, the running speed of the spray head is 1 m / s compared to the CIGS thin film battery chip;
[0047] (3) Covering the corresponding front glass from top to bottom on the adhesive film sprayed with the polystyrene spherical particles 4 in step (2) for lamination;
[0048] (4) After the lamination is completed, a lamination process is performed. The humidity requirement of the lamination process is 50% RH. The specific steps are as follows:
[0049] a. First, vacuumize the machine. The vacuum pressure is -8KPa and the vacuum time is 2min.
[0050] b. Then transfer to the lamination chamber, the temperature of the lamination chamber is 120°C, and the lamination time is 12 minutes;
[0051] c. Then transfer to the hot pressing chamber for hot pressing. The temperature of the hot pressing chamber is 150°C and the hot pressing time is 11 minutes;
[0052] d. Finally, transfer to the cold pressing chamber for cold pressing. The temperature of the cold pressing chamber is 50°C and the cold pressing time is 8 minutes.
[0053] Embodiment three:
[0054] See also Figure 1 A solar thin-film battery comprises a front glass layer 1, a film layer 2, and a CIGS thin-film battery chip layer 3 stacked in sequence from top to bottom, wherein the film layer 2 has a thickness of 0.7 mm, and polystyrene spherical particles 4 are evenly distributed in the film layer 2, and the polystyrene spherical particles 4 are distributed in the film layer 2 in a single layer.
[0055] The coefficient of variation CV of the particle size of the polystyrene spherical particles 4 in the adhesive film layer 2 is less than 3.5%.
[0056] The particle size of the polystyrene spherical particles 4 in the adhesive film layer 2 is between 900 and 1000 μm.
[0057] The amount of polystyrene spherical particles 4 added to the adhesive film layer 2 is: 30 g of polystyrene spherical particles 4 per square meter of the adhesive film layer 2 .
[0058] The above-mentioned method for preparing a solar thin film battery comprises the following steps:
[0059] (1) First, a CIGS thin film battery chip is prepared, and then an adhesive film is laid on the CIGS thin film battery chip to form an adhesive film layer 2;
[0060] (2) According to the width of the film layer 2, an appropriate number of special spray heads are arranged at equal intervals above the film layer 2 to ensure that the spraying working surfaces of all the film spray heads are sufficient to evenly and completely cover the width of the entire film layer 2, and then the polystyrene spherical particles 4 are evenly sprayed on the surface of the film layer 2 through a number of special spray heads. During the spraying process, the running speed of the spray head is 1 m / s compared to the CIGS thin film battery chip;
[0061] (3) Covering the corresponding front glass from top to bottom on the adhesive film sprayed with the polystyrene spherical particles 4 in step (2) for lamination;
[0062] (4) After the lamination is completed, a lamination process is performed. The humidity requirement for the lamination process is 75% RH. The specific steps are as follows:
[0063] a. First, vacuumize the air with a pressure of -1KPa and a vacuum time of 3 minutes;
[0064] b. Then transfer to the lamination chamber, the temperature of the lamination chamber is 135°C, and the lamination time is 15 minutes;
[0065] c. Then transfer to the hot pressing chamber for hot pressing. The temperature of the hot pressing chamber is 165°C and the hot pressing time is 15 minutes;
[0066] d. Finally, transfer to the cold pressing chamber for cold pressing. The temperature of the cold pressing chamber is 75℃ and the cold pressing time is 12 minutes.
[0067] In the above embodiments, the adhesive film includes but is not limited to EVA adhesive film, POE adhesive film, etc., the CIGS thin-film battery chip adopts but is not limited to copper indium gallium selenide process, cadmium telluride process, crystalline silicon process, perovskite process, etc., and the front glass adopts tempered glass coated with an anti-reflection film.
[0068] After the process according to the above embodiment is completed, it is still necessary to install a split junction box, which is a prior art well known to those skilled in the art and will not be described in detail here.
[0069] In order to verify the beneficial effects of the present invention, the following comparative experiments were performed:
[0070] 1. Comparison of component adhesion test data. The data results are shown in Table 1. The data line chart is shown in Figure 2 :
[0071] The solar thin-film battery produced by encapsulation using the solution in Example 1 of the present application is a newly invented process component. The production process of the normal process component is the same as the solution in Example 1 except that the polystyrene spherical particles are not added.
[0072] Table 1:
[0073]
[0074] 2. Comparison of component power test data. The data results are shown in Table 2. The data scatter plot is shown in Figure 3 :
[0075] The solar thin-film battery produced by encapsulation using the solution in Example 2 of the present application is a newly invented process component. The production process of the normal process component is the same as the solution in Example 2 except that the polystyrene spherical particles are not added.
[0076] Table 2:
[0077]
[0078] 3. Comparison of component power attenuation rates. The data results are shown in Table 3. The data scatter plot is shown in Figure 4 :
[0079] The solar thin-film battery produced by encapsulation using the solution in Example 3 of the present application is a newly invented process component. The production process of the normal process component is the same as the solution in Example 3 except that the polystyrene spherical particles are not added.
[0080] Table 3:
[0081]
Claims
1. A solar thin film battery, characterized in that: It comprises a front plate glass layer, a film layer and a CIGS thin film battery chip layer stacked in sequence from top to bottom. The film layer has a thickness of 0.2 to 0.7 mm. The film layer is provided with evenly distributed polystyrene spherical particles, which are distributed in a single layer in the film layer.
2. A solar thin film battery according to claim 1, characterized in that: The coefficient of variation CV of the particle size of the polystyrene spherical particles in the film layer is less than 3.5%.
3. A solar thin film battery according to claim 1, characterized in that: The particle size of the polystyrene spherical particles in the adhesive film layer is between 50 and 1000 μm.
4. A solar thin film battery according to claim 1, characterized in that: The added amount of the polystyrene spherical particles in the adhesive film layer is: 15 to 30 g of polystyrene spherical particles per square meter of the adhesive film layer.
5. A method for preparing a solar thin film battery according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) First, a CIGS thin-film battery chip is prepared, and then an adhesive film is laid on the CIGS thin-film battery chip to form an adhesive film layer; (2) According to the width of the film layer, an appropriate number of special spray heads are arranged at equal intervals above the film layer to ensure that the spraying working surfaces of all the film spray heads are sufficient to evenly and completely cover the width of the entire film layer, and then the polystyrene spherical particles are evenly sprayed on the surface of the film layer through a number of special spray heads. During the spraying process, the running speed of the spray head is 1 m / s compared to the CIGS thin-film battery chip; (3) Laying the corresponding front glass from top to bottom on the adhesive film sprayed with polystyrene spherical particles in step (2); (4) After the lamination is completed, a lamination process is performed. The humidity requirement of the lamination process is 30% to 75% RH. The specific steps are as follows: a. First, vacuumize the air. The vacuum pressure is -15Kpa~-1KPa and the vacuum time is 1~3min; b. Then transfer to the lamination chamber, the temperature of the lamination chamber is 95-135°C, and the lamination time is 9-15 minutes; c. Then transfer to the hot pressing chamber for hot pressing, the temperature of the hot pressing chamber is 140-165°C, and the hot pressing time is 8-15 minutes; d. Finally, transfer to the cold pressing chamber for cold pressing. The temperature of the cold pressing chamber is 20-75°C and the cold pressing time is 6-12 minutes.
Citation Information
Patent Citations
Packaging adhesive film for solar cell
CN101820001B